An Error Analysis of Phrasal Verb Mistake Based on Surface Strategy Taxonomy In Writing An English Essay - yosi Marita (Edu-Ling: Journal of English Education and Linguistics, 2020)
The purpose of this study was to find and analyze phrasal verb mistake based on surface strategy taxonomy in English essays written by students. This research was conducted using a qualitative approach with content analysis methods. The data source of this research is the first semester students of the Accounting Program Prof. Dr. Hazairin, SH University in academic year 2019/2020. The data consisted of 24 essays written by students. The results of this study indicate that there are 76 errors from four categories of errors including: obmission, misformation, addition, and misordering. Based on the research findings, it can be concluded that the highest error is found in misformation namely 30 times (86%). Causing a misperception between the writer and the reader. Therefore phrasal verb is indispensable in writing essays in English.